ANALYSIS OF PHARMACEUTICAL SUPPORRT OF ONCOLOGICAL PATIENTS WITH NARCOTIC ANALGESICS IN THE OUTPATIENT SETTING IN NIZHNI NOVGOROD - S. V. Kononova; M. V. Lebedeva (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
The article presents the analysis of pharmaceutical support of oncological patients with narcotic analgesics for reversal of chronic pain syndrome at the terminal stage, at the outpatient treatment in Nizhni Novgorod oblast for 2011-2013. Injection forms of morphine hydrochloride and promedol were the principal drugs which are applied by this patient group. We have noted the deficit of strong opioid analgesics in non-invasive forms. The support of incurable oncological patients with narcotic analgesics for the analyzed period averagely amounted to 6.33%.